PENGARUH PROFITABILITAS, LEVERAGE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Setyabudi, Teguh Gunawan (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
The existence of competition requires companies to make various efforts to maintain the existence of the company and increase company value. The company value is indicated by the company's stock price. The purpose of this research is to prove empirically the effect of profitability, leverage and institutional ownership on firm value with dividend policy as an intervening variable. The research data is secondary data in the form of financial statement data and annual reports of companies belonging to the manufacturing industry listed on the Indonesia Stock Exchange for the period 2016 to 2018, totaling 138 companies. Data analysis used path analysis. The results showed that profitability, leverage and institutional ownership had a significant effect on dividend policy. The variables of profitability, leverage and dividend policy are proven to have a significant effect on firm value, while institutional ownership has no effect on firm value. The dividend policy variable is able to moderate the effect of profitability on firm value, but it is not able to moderate the effect of leverage and institutional ownership on firm value.